Reports from the Field: Enhancing ICT Adoption and Use through Change Leadership: Technology Stewardship Training for Caribbean Agricultural Communities of Practice - Gordon Gow (Commonwealth of Learning, 2018)
Beginning in 2012, the University of Alberta in partnership with others has been undertaking participatory action research in Sri Lanka and, since 2017, in the Caribbean to foster inclusive innovation through a Joint Education and Training Initiative (JETI). The JETI is developing and testing a set of open educational resources on “technology stewardship” for resource-constrained organizations and communities in developing countries. The approach is a unique combination of social learning centred on communities of practice with action research methods intended to foster self-determination through improved “informational capabilities” as the primary outcome of development. In this article, we describe the learning objectives, design, observations, and initial outcomes of a pilot technology stewardship training course offered at the University of the West Indies in March 2018. Future plans and considerations for expanding technology stewardship training are discussed in the summary.